To Wong Foo, thanks for everything, Julie Newmar [videorecording (DVD)] - Kidron, Beeban; Snipes, Wesley; Swayze, Patrick; Leguizamo, John; Channing, Stockard; Danner, Blythe (Universal, 2002)
En route from New York City to Hollywood for a drag queen beauty pageant, Noxeema, Vida and Chi Chi are stranded in a tiny Midwestern town when their 1967 Cadillac breaks down. When their glitz and glamour wake up the sleepy local citizens, the stage is set for an outrageously funny weekend.